Alkyl‐Chain‐Separated Triphenybenzene ‐ Carbazole Conjugates and their Derived Polymers: Candidates for Sensory, Electrical and Optical Materials. Issue 21 (21st December 2016) - Kaleeswaran, D.; Vishnoi, Pratap; Kumar, Subramani; Chithiravel, Sundaresan; Walawalkar, Mrinalini G.; Krishnamoorthy, Kothandam; Murugavel, Ramaswamy
Abstract: Four new triphenylbenzene based carbazoles (THPBCz4, THPBCz6, THPBCz8 and THPBCz10) and polycarbazoles (polyTHPBCz4, polyTHPBCz6, polyTHPBCz8 and polyTHPBCz10), have been synthesized. Photoluminescence spectra of the monomers in dichloromethane exhibit two intense bands at 353 and 369 nm. Two additional bands (410 and 435 nm) are also observed due to intermolecular interactions. These bands are more intense in the case of thin films, indicating stronger π‐π stacking interactions in the solid state. Due to the extended π‐conjugation, the polycarbazoles display two main emission bands (495 and 520 nm) which are red shifted as compared to the monocarbazoles. Due to the presence of emissive platforms such as triarylbenzene and carbazole, both monomers and polymers, function as efficient sensors for the detection of polynitroaromatic analytes (PA, DNT, p ‐DNB and m ‐DNB). The electrochemically polymerized carbazole derivatives showed maximum capacitance of 41 F/g for polyTHPBCz6. The SCLC measurement reveals a maximum mobility of 6 x 10 −6 cm 2 /Vs for polyTHPBCz4 that showed better packing due to flexible alkyl chains that connect the conjugated moieties. Abstract : Three‐in‐one: Alkyl chain separated emissive triphenylbenzene based carbazoles and polycarbazoles were designed and developed. The emissive nature of the compounds was quenched by the polynitroaromatic compounds in solution as well as in thin film. Further, the electrochemically polymerized carbazoles were exhibiting moderate super capacitance behaviour and charge carrier mobility.